Association Between Methylenetetrahydrofolate Reductase Gene Polymorphisms and Risk of Vitiligo: A Systematic Review and Meta-Analysis - Hua-Ching Chang; Ming-Hsiu Lin; Hsiou-Hsin Tsai (Medical Journals Sweden, 2020)
Abstract is missing (Short communication)